Retour sur une recherche pluridisciplinaire autour de l’agriculture dans les Andes Centrales (altiplano bolivien) - Jean-Joinville Vacher; Carmen Del Castillo (Revue d'ethnoécologie)
The Bolivian altiplano, located around 4000 m, presents very high risks of drought and frost for crops. However, it is one of the main potato-producing regions of the Andes, food base of the rural population. Potato farming results from the combination of four interdependent components with, in the first place, the use of a multi-specific diversity of six species of Solanum, of which the most cultivated Solanum tuberosum subsp. andigenum, S. juzepczukii and S. curtilobum show a wide range of adaptations to agroclimatic stresses and variability. Crops benefit at the same time from a very significant spatial heterogeneity of the risks of frost and drought at the scales of the region, the farm and the field, known and valued by farmers in the different potato crop steps. Community management of agricultural space also allows each farmer to have access to all of the diversity of agro-ecological situations in the community. Finally, the sustainability of a thousand-year-old tuber freeze-drying technique allows the consumption and agriculture of S. juzepczukii and S. curtilobum with high glycoalkaloid contents, and improves food safety with the chuño, an easily transportable product that can be store for more than ten years.